PENANAMAN SIKAP PEDULI SOSIAL PADA GENERASI MUDA MELALUI ORGANISASI KARANG TARUNA DESA RANTAU PANJANG - Darmawan Darmawan; Achmadi Achmadi; Thomy Sastra Atmaja (Universitas Tanjungpura, 2023)
This study aims to determine the inculcation of social care attitudes in the younger generation in Rantau Panjang Village. This form of research uses qualitative research with descriptive methods. The sources of data in this research are the Karang Taruna organization's management, the village head, and the younger generation. Data obtained through observation, interviews and documentation. The results of the study explained that the management of the youth organization was successful in instilling a socially caring attitude in the younger generation. This success can be seen from several forms of activity implementation such as fundraising activities, giving compensation to people in need, working together to clean the environment and sports facilities, painting the gates of boundaries between hamlets, and working together in packing groceries, establishing cooperative relationships with other institutions/agencies, commemorating Islamic holidays in the form of echoes of takbir and torchlight parades in welcoming Eid al-Fitr, and carrying out soccer tournament activities in the Village Head trophy. In their involvement, the management of the youth organization gives a role to the younger generation to carry out various activities. It is from this role that a personality attitude to care for one another towards fellow social beings can be formed.